1988
DOI: 10.1063/1.341629
|View full text |Cite
|
Sign up to set email alerts
|

The inversion of surface potential measurements to determine crack size and shape

Abstract: The ac field measurement technique (acfm) for sizing surface breaking cracks in metals exploits the fact that the high-frequency alternating current tends to flow in a thin skin on the metal and crack surfaces. The method seeks to interpret measured perturbations in the surface voltages produced by a crack so as to deduce its size and its shape and for this purpose a suitable mathematical model of the field is required. In the past, solutions of direct problems in which the crack shape is assumed to be known h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The together use of physical measurement and filed modelling allows the exclusion of calibration procedure, which minimises possible errors occurring during calibration activities applied by other NTD methods [30][31][32]35]. Inverse problems associated with crack profile determination have been solved with numerical iterative procedures [54]. With respect to small crack sizing ability, it has been reported that ACPD was preferred in monitoring long shallow surface cracks but lost accuracy in cases of deep surface cracks that could be accurately predicted by ACFM [30].…”
Section: Alternating Current Field Measurementmentioning
confidence: 99%
“…The together use of physical measurement and filed modelling allows the exclusion of calibration procedure, which minimises possible errors occurring during calibration activities applied by other NTD methods [30][31][32]35]. Inverse problems associated with crack profile determination have been solved with numerical iterative procedures [54]. With respect to small crack sizing ability, it has been reported that ACPD was preferred in monitoring long shallow surface cracks but lost accuracy in cases of deep surface cracks that could be accurately predicted by ACFM [30].…”
Section: Alternating Current Field Measurementmentioning
confidence: 99%
“…Quantitative measurement of cracks and defects based on the application of inverse analysis has been made by a lot of researchers using D.C. or A.C. electric potential method [1][2][3][4][5], ultrasonic method [6,7], elastodynamic method [8] and strain measurement [9], etc. Recently, crack detection has been regarded as one of the inverse problems.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, this latter assumption is not particularly restrictive, as it is possible to locate the crack tips by considering the variation in the voltage signal as a probe moves along the length of the crack. In a concurrent study (Connolly et 1988), this problem has also been considered by using an iterative technique. Their method requires an initial guess of the crack shape to be made using the one-dimensional estimate.…”
Section: Introductionmentioning
confidence: 99%